The Influence of Work Discipline and Non-Physical Work Environment on Employee Performance: Case Study in One of The Local Government Institutions in The City of Bandung - Dita Aulia; Retno Resawati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
The researcher conducted a study to understand the impact of work discipline and non-physical work environment on employee performance in a local government agency in Bandung. Additionally, this research aims to analyze the most dominant factors influencing employee performance between work discipline and the non-physical work environment in this particular local government agency being studied. The researchers interviewed 65 employees using questionnaires. The research using path analysis found that the variables of work discipline and non-physical work environment in one of the local government agencies in the city of Bandung are valid. The conclusions and considerations regarding the research results emphasize the importance of paying attention to work discipline and non-physical work environment to enhance employee performance. The research findings indicate that Work Discipline (X1) significantly influences Employee Performance (Y). Furthermore, the Non-Physical Work Environment (X2) also significantly influences Employee Performance (Y). To improve work discipline in one of the local government agencies in Bandung, we recommend that supervisors allocate time to supervise the implementation of company tasks and impose appropriate sanctions on employees who violate discipline. Leaders must pay attention to and be aware of any violations committed by anyone without discrimination among the employees. The company should also provide recognition to employees who perform well to enhance their performance. To improve the non-physical work environment, the researcher recommends organizing events or activities that can strengthen the relationship between employees and superiors, fostering mutual assistance and care among them. The local government agency should also maintain leaders who provide technical assistance to subordinates when they face difficulties, as it will significantly assist other employees.